AUTOETNOGRAFIA DE UMA FORMAÇÃO: CURRÍCULO E PRÁTICAS PEDAGÓGICAS DECOLONIAIS NO CURSO DE PEDAGOGIA DA UNILAB-CEARÁ - MIRANDA, FELIZBELA KUYELA ALBERTO (2023)
The educational reality of territories that went through European colonial processes reflects the legacy projected for centuries by their civilizations, it is an education that distanced countless people from their roots, their true History, their ancestry and their essence, an education based on policies assimilationists and segregationists. This distance is understood when we note that in addition to the evangelization and catechization that were fundamental in the construction and establishment of racial and cultural discrimination, European colonial educational processes aimed to establish and implement the belief in the superiority of the white race. This work addresses discussions focused on the educational reality of territories that went through Portugal's colonial processes, bringing a reflection on the application of educational curricula that manipulate being and knowledge, which validate education as an elitist and capitalist activity. These curricula have been essential for implementing the culture of competition and hierarchy, valuing high performance and rewarding those who have high performance, and who have neglected inclusive and humanized teaching. During the discussions brought in this work, we will observe that issues related to the curricular constructions of countries colonized by Portugal still suffer a lot of influence from the conservative elite, since they feel they have the right to control and determine what can or cannot be taught and when or how certain topics should be addressed. For some decades, discussions have arisen in the sociocultural, historical and psychological fields of different regions of the world that have reflected the damage caused by European colonization, discussions that have exposed the great need to break with Eurocentric structures and paradigms of exclusion. One of the fundamental allies in this reflective and deconstruction process has been decolonial education, an education that highlights the need and importance of the fight against coloniality in socio-educational practices and which has become a crucial means in the process of transformation and renewal of minds, this, for adding and contemplating in their curricula the diversity, cultural and identity development of individuals within their universes. Amidst the struggle for the recognition and inclusion of Afro and indigenous history and culture in educational processes, the University of International Integration of Afro-Brazilian Lusofonia (UNILAB) was born in Brazil, created under the application of the support program for restructuring and expansion of Federal Universities - Reuni and South-South cooperation, this project aims to promote the development of regions that still lack higher education institutions in Brazil. Based on the principles of solidarity cooperation and characterized by international cooperation, academic and solidarity exchange with CPLP member countries, namely Angola, Cape Verde, Guinea-Bissau, Mozambique, São Tomé and Príncipe and East Timor, UNILAB has worked to the formation of citizens capable of multiplying learning through the development of research in different areas of knowledge and the innovative promotion of university extension. Among the courses at this institution we have the object of study of this work, the degree course in Pedagogy at UNILAB, a course that has a different curriculum from other Pedagogy courses in Brazil and the Integration Countries (Angola, Cape-Verde, Guinea - Bissau, São Tomé and Príncipe, Mozambique and East Timor). Therefore, we will reflect through discussions of works by mostly black and Afro-centered authors, the author's autoethnographic report, the analysis of the Curricular Political Plan of the Bachelor's degree in humanities and Degree in Pedagogy courses and the analysis curriculum of nine subjects of the UNILAB Pedagogy course, the relevance and impact of training Afro-referenced teachers in Integration countries, thus contributing to discussions on the inclusion of Afro-Brazilian history and culture. indigenous people in educational processes, decolonization of the Curriculum and teacher training for difference, an essential element in the implementation of an inclusive educational system.